NLRC5 elicits antitumor immunity by enhancing processing and presentation of tumor antigens to CD8+ T lymphocytes. (2nd June 2016) - Rodriguez, Galaxia M.; Bobbala, Diwakar; Serrano, Daniel; Mayhue, Marian; Champagne, Audrey; Saucier, Caroline; Steimle, Viktor; Kufer, Thomas A.; Menendez, Alfredo; Ramanathan, Sheela; Ilangumaran, Subburaj
ABSTRACT: Cancers can escape immunesurveillance by diminishing the expression of MHC class-I molecules (MHC-I) and components of the antigen-processing machinery (APM). Developing new approaches to reverse these defects could boost the efforts to restore antitumor immunity. Recent studies have shown that the expression of MHC-I and antigen-processing molecules is transcriptionally regulated by NOD-like receptor CARD domain containing 5 (NLRC5). To investigate whether NLRC5 could be used to improve tumor immunogenicity, we established stable lines of B16-F10 melanoma cells expressing NLRC5 (B16-5), the T cell co-stimulatory molecule CD80 (B16-CD80) or both (B16-5/80). Cells harboring NLRC5 constitutively expressed MHC-I and LMP2, LMP7 and TAP1 genes of the APM. The B16-5 cells efficiently presented the melanoma antigenic peptide gp10025–33 to Pmel-1 TCR transgenic CD8 + T cells and induced their proliferation. In the presence of CD80, B16-5 cells stimulated Pmel-1 cells even without the addition of gp100 peptide, indicating that NLRC5 facilitated the processing and presentation of endogenous tumor antigen. Upon subcutaneous implantation, B16-5 cells showed markedly reduced tumor growth in C57BL/6 hosts but not in immunodeficient hosts, indicating that the NLRC5-expressing tumor cells elicited antitumor immunity. Following intravenous injection, B16-5 and B16-5/80 cells formed fewer lung tumor foci compared to control cells. In mice depleted of CD8 + T cells, B16-5 cells formed large subcutaneous and lung tumors. Finally, immunization with irradiated B16-5 cells conferred protection against challenge by parental B16 cells. Collectively, our findings indicate that NLRC5 could be exploited to restore tumor immunogenicity and to stimulate protective antitumor immunity.